Pengaruh Komunikasi, Disiplin Kerja, dan Lingkungan terhadap Kinerja Karyawan pada CV. Asia Mega Mas - Steven Gilbert Bakara; Yarni Waruwu; Novitria Ningsih Lase; Aswince Gulo; Natanael Simanjuntak; Maduma Sari Sagala (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
The problem in this study is the lack of communication between superiors and employees. There are still employees who are not disciplined in company regulations, the physical work environment at CV. Asia Mega Mas is inadequate and employee performance appraisal data has decreased from 2021-2023. The purpose of this study is to determine the effect of communication, work discipline and work environment on employee performance at CV. Asia Mega Mas. The type of research is quantitative. The population in this study is employees of CV. Asia Mega Mas totaling 48 samples while the sampling technique uses the saturated sampling method. The sources in this study come from primary data and secondary data. The data collection method uses observation, interviews, questionnaires and documentation. The data analysis technique used is multiple linear regression. Data processing is assisted by the SPSS version 25 tool. The results of the (t) test or partial test show that the communication variable (0.001) is greater than the alpha 5% (0.05) or t count = 3.561> t table 2.015. The work discipline variable (0.000) is greater than the alpha 5% (0.05) or t count = 4.168> t table 2.015. And the environmental variable (0.009) is greater than the alpha 5% (0.05) or t count = (-2.728)> t table 2.015. Then simultaneously the (F) test significant value F is smaller than 5% or 0.05 or the f count value = 36.243> F table 2.82. The results of the determination coefficient (R2) The adjusted R Square value is 0.692 (69.2%). So it can be said that 69.2% of the variation in communication, work discipline and environment variables in the model can explain employee performance variables, while the remaining 31.8% is influenced by other variables outside the model.